1970
DOI: 10.1002/jez.1401750405
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian lung development: Interactions in formation and morphogenesis of tracheal buds

Abstract: Mesoderm present in early developing lung is of two sorts: bronchial, which can evoke formation of bronchial buds from tracheal epithelium; and tracheal, which inhibits bronchial morphogenesis. The latter process correlates with the presence of highly ordered sheaths of collagen and mesoderm cells near the epithelial surface. In contrast, bronchial mesoderm lacks such regularly arrayed components. Initial formation of supernumerary buds on the trachea can be evoked by nonspecific mesoderms, but such buds never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(108 citation statements)
references
References 11 publications
2
105
0
1
Order By: Relevance
“…However, it is becoming clear that different fibroblast can have distinct functions. For example, during lung development, epithelial induction capacities are known to differ based on whether the mesenchyme is derived from the trachea or the tips of the growing lungs 69 . The origin of the mesenchymal fibroblasts apparently determines their sensitivity to sonic hedgehog (Shh) derived from the developing lung epithelia.…”
Section: Not All Fibroblasts Are Created Equalmentioning
confidence: 99%
“…However, it is becoming clear that different fibroblast can have distinct functions. For example, during lung development, epithelial induction capacities are known to differ based on whether the mesenchyme is derived from the trachea or the tips of the growing lungs 69 . The origin of the mesenchymal fibroblasts apparently determines their sensitivity to sonic hedgehog (Shh) derived from the developing lung epithelia.…”
Section: Not All Fibroblasts Are Created Equalmentioning
confidence: 99%
“…The embryonic airway epithelium is highly proliferative in vivo (21), and it is often assumed that new branches result from localized growth (22). We therefore quantified 3D patterns of proliferation within mesenchyme-free explants ( Fig.…”
Section: Spatial Patterns Of Proliferation Do Not Appear Until Branchmentioning
confidence: 99%
“…Then epithelia alone or in combination with homologous or heterologous mesenchyme were cultured in vitro or grafted into the anterior eye chamber or under the kidney capsule. It was concluded that the mesenchyme plays critical roles in organogenesis in kidney (5), pancreas (6,7), tooth (8,9), mammary gland (10), lung (11), gastrointestine (12), male urogenital tract (13,14), and female reproductive tract (15,16) tissues. In the 1970s, a search for epithelial cell-fate-determining factors of mesenchymal origin was begun, but has been without success (17)(18)(19).…”
mentioning
confidence: 99%